Influence of Language Preference on Vocabulary Proficiency and Reading Comprehension of Selected Grade 10 Bilingual Students at MSU Sulu Laboratory High School - Tantalie, Edwin M. (RA Journal of Applied Research, 2021)
The primary purpose of this study is to determine the influence of language preference on bilingual student’s vocabulary and reading comprehension among selected Grade 10 students of the Mindanao State University- Sulu Laboratory High School. The respondents were taken from Grade 10 classes with a total of ninety (99) student respondents. The data consisted of the scores of vocabulary proficiency test and reading comprehension test administered to the pupils. Furthermore, this study made use of a standardized test for vocabulary proficiency and reading comprehension. This study made use of the descriptive-quantitative research design to determine the influence of language preference on student’s vocabulary and reading comprehension among the bilingual Grade 10 students of the Mindanao State University-Sulu Laboratory High School. This study yielded the following findings: (1) Majority of the Grade 10 students of Mindanao State University-Sulu Laboratory High School prefer to use their vernacular language or lingua franca (L1), Bahasa Sug and English; (2) The level of vocabulary proficiency of bilingual Grade 10 students of Mindanao State University- Sulu Laboratory High School is proficient to advance levels; (3) No significant relationship exists between language preference and vocabulary proficiency of bilingual Grade 10 students of Mindanao State University- Sulu Laboratory High School; (4) The level of reading comprehension of bilingual Grade 10 students of Mindanao State University- Sulu Laboratory High School is proficient to advance levels; (5) There is no significant correlation between language preference and reading comprehension of bilingual Grade 10 students of Mindanao State University- Sulu Laboratory High School; and (6) There is no significant relationship between vocabulary proficiency and reading comprehension of bilingual Grade VI pupils. Based on the findings, it can be concluded that there is no significant relationship between language preference and vocabulary proficiency and likewise for language preference and reading comprehension of bilingual Grade 10 students. This only draws one conclusion that language preference of bilingual Grade 10 students does not influence the bilingual children’s vocabulary proficiency and reading comprehension. This finding invites possible evaluations and further studies of the Grade 10 curriculum, empowering English language, and pupil-related factor to determine the outlook of the pupils. Based on the said findings, the researcher would like to recommend the following: (1) This study would help future researchers which will comprehensively assist the pupils for a more effective and relevant vocabulary and reading enhancement activity to advance their skills; (2) This study would aid future studies that will explore the factors regarding the influence of language preference on children’s vocabulary proficiency and reading comprehension; and (3) This study would serve as an appraisal of enhancing to advance the skills of the children on vocabulary proficiency and reading comprehension.